An analysis of housing location attributes in the inner city of Budapest, Hungary, using expert judgements - Tom Kauko (International Journal of Strategic Property Management, 2007)
The role of location quality in housing consumption is an increasingly important research objective given the demand‐side considerations stemming from economic and socio‐cultural changes in urban and metropolitan housing market areas. In circumstances involving diversified demand, the consumption pattern comprises a set of different preference profiles. From an operational point of view, such outcome can be generated through ranking location attributes with respect to their relative importance for the house buyer or renter. This procedure may, for example, be based on pair‐wise comparison of attributes based on expert judgements and the analytic hierarchy process (AHP). This study is based on expert elicited residential location quality profiles in the inner city of Budapest, and builds on prior work on housing market analysis reported elsewhere. Here the particular issue, typical for post‐communist circumstances, concerns a mismatch between the range of available product groups and the increasingly quality conscious and differentiated buyer preferences.